Framework Administered Account for Selected Fund Activities : Central African Regional Technical Assistance Center (AFRITAC Central) Subaccount. (Policy Papers; Policy Paper ;, 2010)
This supplement provides clarifications and proposes revision to the reforms of the nonconcessional lending toolkit contained in the staff papers on 'The Fund's Mandate-Future Financing Role: Reform Proposals'. The focus of this supplement is on the Flexible Credit Line (FCL) and the Precautionary Credit Line (PCL), for which revised proposed decisions are attached.